Dispersion of Aculops lycopersici (Tryon) (Acari : Eriophyoidea) on tomato leaves and stems - Haque, Mohd. Mainul; Kawai, Akira (University Journal of Zoology, Rajshahi University, 2007)
Key words: Aculops lycopersici; dispersion, tomato plants; leaves and stems Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 19-22